Implementasi Metode Latihan Berjenjang Dalam Pembelajaran Lompat Jauh Untuk Atlet Usia Dini - Muh. Yasa; La Ode Ahmad Yusran (Journal of Humanities, Social Sciences, and Education, 2025)
Long jump training for young athletes requires a systematic, structured approach that aligns with the characteristics of the child's physical and psychological development. One strategy considered effective in developing technical and fundamental movement skills is the graduated training method. This literature review aims to analyze the implementation of the graduated training method in long jump training for young athletes. The analysis was conducted through a review of various recent scientific sources discussing motor skill development, graduated training, and long jump technique instruction for beginners.The study results indicate that the graduated training method significantly contributes to improving athletes' understanding of basic techniques, motor coordination, muscle strength, and consistent performance. The training model, which progresses from simple to complex stages, such as basic running, the start, the takeoff, the glide, and the landing, has been shown to help young athletes gradually adapt to the demands of long jump technique without causing excessive physical and mental stress. Furthermore, the graduated approach also strengthens athletes' motivation and self-confidence, thus supporting long-term performance. Therefore, the graduated training method is recommended as a relevant and effective learning strategy for early-age long jump training.